Estimated class «A» pan coefficients to calculate the reference crop evapotranspiration in the south of Uruguay - Puppo, L.; García Petillo, M. (Agrociencia Uruguay, 2009)
The objective was to estimate the local pan coefficients (Kp) to calculate the reference crop evapotranspiration according to Penman-Monteith modified by FAO (FAO-PM ETo). The climatic data used correspond to 34 years (1975-2008) and were taken from the Estación Experimental INIA Las Brujas (EELB), which is representative of the south of the country. Even years were used to calibrate a Kp for each month and for each year (Kp-calibrated) and the odd years were used for validation. Four alternative methods were tested to estimate ETo, using the following equation: ETo = Eo x Kp. Where Eo corresponds to the monthly pan evaporation. Evaluated Kp coefficients were: Kp-FAO; Kp-Corsi; Kp-calibrated and Kp calculated as the average of the Kp calibrated obtained in the period OctoberApril. To evaluate the adjustment of the four methods, the values of the estimated from the monthly Eo values corresponding to odd years and its Kp were compared with the standard method (FAO-PM ETo) for the same years, by the t-Student test for matched up data (α= 0.05). The use of calibrated Kp gave the best estimation of FAO-PM ETo. The Kp was 0.71 and its use during the irrigation season allowed a good estimation for the south of the country. The use of this unique coefficient to correct the pan evaporation data is a simple and easy tool to adopt by the farmers, and constitutes a good estimation of the ETo.